OBTAINING OF ECHINOCOCCUS GRANULOSUS IN EXPERIMENTALLY INFECTED DOGS WITH PROTOSCOLICES OF HYDATID CYSTS - Rosales G., Sofía (2008)
The objective of the present study was to experimentally reproduce the biological cycle of Echinococcus granulosus in dogs. Twelve dogs, 4-50 months old, were infected with 80,000-308,000 protoscolices recovered from lung and liver hidatyd cysts in sheep reared in the central highlands of Peru. Dogs were slaughtered 28-39 days post infection (p.i) and the small intestine was divided in three equal portions (anterior, medium, and posterior) and parasites were counted. The location of parasites in the three portions of intestine was recorded in three dogs. Eight out of 12 dogs resulted positive to the infection and the number of parasites varied from 1,299 till 65,000 per dog. Animals slaughtered on the 28th p.i day resulted negative. The preferred site for parasites was the medium portion of the small intestine. It was shown that the oral inoculation of protoscolices from sheep hydatic cysts was effective to reproduce the biological cycle of the E. granulosus in dogs.